The Antecedents Of Process Innovation And Smes Growth: Empirical Evidence From Shoe Manufacturing Sector In The Ashanti Region Of Ghana - Osei, Abraham; Yunfei, Shao; Appienti, William Ansah; Forkuoh, Solomon Kwarteng (European Scientific Journal, ESJ, 2016)
This article contributes to the study of process innovation as a growth strategy for SMEs, enriching and complementing the widely held view that innovation in general impacts positively on SMEs productivity and growth. In furtherance, this study looks at the process innovation from three main angles as proposed by the Oslo Manuel, which are new process, improved process, and new and improved distribution. Firm level data were purposively collected from shoes manufacturing companies located in the Ashanti Region of Ghana, where Structural Equation Model were employed in coming out with the path estimates in determining the relationship between the variables. The results indicated that, adoption of new and improved distribution strategy impact positively on the growth of the SMEs, by way of reducing the cost of operations and increases customers’ satisfaction. This was followed by the adoption of improved process strategy, where the productivity saw a massive improvement in the areas of quality and quantity, but there was no significance in the reduction of cost of production, whereas the adoption of new process strategy saw an increase in production, but its associated high cost of production negated the growth, to impact negatively on the growth of the SMEs. Base on the results from the study, our results suggest that adoption of process innovation have significant effect on the performance of the shoes manufacturing, the positive impact is not a wholesale, therefore entrepreneurs should not adopt all process innovation blanketly.